Noble gas neuroprotection: xenon and argon protect against hypoxic–ischaemic injury in rat hippocampus in vitro via distinct mechanisms. (November 2019) - Koziakova, Mariia; Harris, Katie; Edge, Christopher J.; Franks, Nicholas P.; White, Ian L.; Dickinson, Robert
Abstract: Background: Noble gases may provide novel treatments for neurological injuries such as ischaemic and traumatic brain injury. Few studies have evaluated the complete series of noble gases under identical conditions in the same model. Methods: We used an in vitro model of hypoxia–ischaemia to evaluate the neuroprotective properties of the series of noble gases, helium, neon, argon, krypton, and xenon. Organotypic hippocampal brain slices from mice were subjected to oxygen-glucose deprivation, and injury was quantified using propidium iodide fluorescence. Results: Both xenon and argon were equally effective neuroprotectants, with 0.5 atm of xenon or argon reducing injury by 96% ( P <0.0001), whereas helium, neon, and krypton were devoid of any protective effect. Neuroprotection by xenon, but not argon, was reversed by elevated glycine. Conclusions: Xenon and argon are equally effective as neuroprotectants against hypoxia–ischaemia in vitro, with both gases preventing injury development. Although xenon's neuroprotective effect may be mediated by inhibition of the N -methyl-d -aspartate receptor at the glycine site, argon acts via a different mechanism. These findings may have important implications for their clinical use as neuroprotectants.